Outcomes of Six-Dose High-Dose Cytarabine as a Salvage Regimen for Patients with Relapsed/Refractory Acute Myeloid Leukemia - Brandi Anders; Lauren Veltri; Abraham S. Kanate; Alexandra Shillingburg; Nilay Shah; Michael Craig; Aaron Cumpston (Advances in Hematology)
Relapsed/refractory acute myeloid leukemia (RR-AML) is associated with poor prognosis and long-term disease-free survival requires allogeneic hematopoietic cell transplantation (allo-HCT). Limited data exists, regarding the optimal regimen to obtain remission prior to allo-HCT. Single agent high-dose cytarabine (10–12 doses administered every 12 hours) has been previously used as induction therapy. Six-dose high-dose cytarabine (HiDAC-6), commonly used as a consolidation regimen, has never been evaluated as induction therapy. We present a retrospective review of 26 consecutive patients with RR-AML receiving single agent cytarabine 3 g/m2 intravenously every 12 hours on days 1, 3, and 5 for a total of six doses (HiDAC-6). Median follow-up for surviving patients was 10.4 months (range 1.6–112.2 months). Complete remission was obtained in 62% (54% CR and 8% CRi) of the patients. The median relapse-free survival (RFS) was 22.3 months (range 0.7–112 months), event-free survival (EFS) was 4.7 months (range 0.5–112 months), and the overall survival (OS) was 9.6 months (range 1–112 months). Thirty-five percent of patients were able to subsequently proceed to allo-HCT. Treatment-related toxicities included neutropenic fever (38%), infection (35%), neurotoxicity (8%), and skin toxicity (8%). This is the first study to demonstrate HiDAC-6 as an active treatment option for younger patients with RR-AML which can effectively serve as a bridge to allo-HCT without significant toxicity.